Banaag at sikat metakritisismo at antolohiya - Reyes, Maria Luisa Torres (Manila National Commission for Culture and the Arts, 2010)
Collection of literary criticism of a novel Banaag at Sikat by Lope K. Santos from 1907-1980.
Includes bibliographical references.
Keywords: Santos, Lope K. -- History and criticism; Philippine literature -- History and criticism; Filipino literature -- History and criticism